Patient-Reported Activity Levels Correlate With Early Cartilage Degeneration After Anterior Cruciate Ligament Reconstruction. Issue 2 (February 2021) - Friedman, James M.; Su, Favian; Zhang, Alan L.; Allen, Christina R.; Feeley, Brian T.; Souza, Richard; Li, Xiaojuan; Ma, C. Benjamin; Lansdown, Drew A.
Background: The association between activity level after anterior cruciate ligament (ACL) reconstruction (ACLR) and development of posttraumatic osteoarthritis (PTOA) remains unclear. This study investigated the relationship of patient-reported outcomes and progressive cartilage degenerative changes at 3 years after ACLR. Hypothesis: Higher activity levels, as measured by Marx scores, are significantly correlated with early cartilage degeneration after ACLR. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 35 patients (16 women; mean age, 31.0 ± 7.6 years) with isolated ACLR and without pre-existing arthritis were prospectively enrolled. Patients reported Marx activity scores and Knee injury and Osteoarthritis Outcome Score (KOOS) scores and underwent T1 ρ magnetic resonance imaging (MRI) preoperatively, 6 months, 1 year, 2 years, and 3 years after ACLR with soft tissue graft (22 autograft). The change in cartilage relaxation times between preoperative and 3-year imaging was used to identify cartilage degeneration, defined as an increase in T1 ρ values by 14.3%. Correlation between Marx activity levels, KOOS scores, and T1 ρ degeneration was performed with the Spearman rank test. The Fisher exact test was used to test for association between Marx activity score cutoffs and degeneration. The Student t test was used to compare Whole-Organ Magnetic Resonance Imaging Score (WORMS) and T1 ρ relaxation times. Significance was defined as P < .05. Results: Sixteen patients (45.7%) showed evidence of cartilage degeneration at 3 years, most frequently in the medial compartment (n = 12; 34%). Higher Marx activity scores at 3 years correlated with cartilage degeneration in the medial femur (rho = 0.34; P = .045), and medial tibia (rho = 0.43; P = .01). A Marx score of 11 or greater at 3 years was significantly associated with medial compartment degeneration ( P = .03), with a positive predictive value of 52.6%. No Marx score cutoff at years 1 or 2 predicted future cartilage degeneration. The KOOS Quality of Life score was inversely correlated with cartilage degeneration (rho = 0.38; P = .02). WORMS did not correlate with degeneration of the medial compartment. Conclusion: Increased activity at 3 years after ACLR was significantly associated with increased risk of medial compartment PTOA. While further research is needed to fully define these relationships, patients may be counseled that return to Marx activity levels of greater than 11 may be associated with a higher risk of medial compartment cartilage degeneration.